Abstraction and Artifice - Southcombe, Mark (Architectural History Aotearoa, 2009)
This paper reflects on the architecture of the Wanganui Community Arts Centre 1989, and local, national and international contexts of its design and realisation. It documents and records the project and its history. It advances a reading of the project and its critical aspirations based on personal experience, documentation and the characteristics of the architecture. Finally, with reference to Jan Turnovsky’s The Poetics of a Wall Projection implications of an architect writing history of architecture is reflected on.